Developing a model for successful implementation of affirmative action in the South African public service - Sikakane, Buyiswa Hope (University of the Free State, 1998)
𝑬𝒏𝒈𝒍𝒊𝒔𝒉 During the apartheid era, the South African government introduced and enforced discriminatory policies giving unfair advantage to white people who enjoyed all the privileges. The 1994 national elections meant the demise of an authoritarian government and heralded a transformation process to a democratic, non-racial and non-sexist society where human rights are provided for in the constitution. The new government has introduced affirmative action in order to eliminate employment discrimination and to promote occupational advancement of disadvantaged groups, thus increasing their representativeness in managerial positions. Affirmative action is a topical subject in contemporary South Africa with some groups, especially those who are likely to benefit from the affirming process supporting it, while those who are likely to part with the privileges that they have enjoyed for decades, strenuously rejecting it. However, it has to be borne in mind that affirmative action is a process and not an event. In countries like the United States of America (USA) where affirmative action was first introduced many years ago, it is still not a success story. It needs careful planning and monitoring throughout its implementation in order to identify areas in the process that need to be adjusted or amended. Affirmative action should not be confused with retribution where white people are being punished for the privileges they enjoyed. It does not mean that white employees should be removed from their positions and be replaced by blacks as this may precipitate racial tension and bitterness. Affirmative action requires training and development of members from disadvantaged backgrounds, so that they are ready to move up the occupational ladder. They should take an active part in their own development. The culture of entitlement which plagues the minds of historically disadvantaged groups should be eradicated. They should not think that being beneficiaries of affirmative action entitles them to managerial positions without the necessary qualifications and skills. Each public organization should provide opportunities for training and development of disadvantaged groups, like study leave, financial assistance and on-the-job training. Academic institutions should adjust their curricula to suit the needs of public organizations. Commitment of top management, employees and unions is one of the important ingredients of affirmative action so that all stakeholders may cooperate in devising strategies for successful implementation of affirmative action programme. The culture and mindset of the workplace should change. There should be a change of perceptions and attitudes. It is necessary to depart from the racist belief that anything that is African is inferior. What is needed is appreciation and acceptance of the cultural differences among employees which can contribute towards the effectiveness and productivity of a public organization. The caliber of employees should be considered in order to avoid tokenism and lowering standards. Where the disadvantaged background has deprived some people with potential of certain qualifications and experience, employees who have been selected would be trained in order to unlock their potential. A public organization should, where possible, employ the services of an affirmative action officer or a senior manager who should be assigned the duties of an affirmative action officer. Such an officer should preferably be a member of disadvantaged groups who would command respect and credibility within an organization and be responsible for the day-to-day issues concerning affirmative action. He / she should work with an affirmative action steering committee which should consist of a cross-section of staff with equal representation from all stakeholders. Specific programmes should be developed to eliminate discrimination in all human resource activities like recruitment, selection, promotion, training and development and evaluation. There should be mechanisms to deal with grievances and disputes regarding alleged discrimination. ___________________________________________________________________

𝑨𝒇𝒓𝒊𝒌𝒂𝒂𝒏𝒔 Tydens die apartheid era is 'n diskriminerende beleid deur die Suid-Afrikaanse regering bekendgestel en bekragtig. Daardeur is 'n onregverdige voordeel aan blankes gegee en 'n verskeidenheid van voorregte is geniet. Die nasionale verkiesing in 1994 het die einde van 'n outoritere regering beketen. Gevolglik die begin van 'n transformasieproses tot 'n demokratiese, nie-rassige en nie-seksistiese samelewing. In die nuwe grondwet word voorsiening gemaak vir die beginsel van menseregte. Die nuwe regering het regstellende aksie ingestel sodat diskriminasie by indiensneming tot 'n minimun beperk word. Dit het gelei tot die bevoordeling van benadeelde groepe in die werkplek. Bestuursposisies het daarom meer verteenwoordigend van die groepe geword. Regstellende aksie is 'n aktuele onderwerp onder sekere groepe in die huidige Suid-Afrika. Die groepe wat waarskynlik sal voordeel trek, is ondersteunend ander groepe wat sekere voorregte wat al dekades lank geniet is, moet prysgee, verwerp die proses. Dit moet egter in gedagte gehou word dat regstellende aksie 'n proses is en nie 'n gebeurtenis nie. In lande soos die Verenigde State van Amerika (VSA), waar regstellende aksie jare terug bekendgestel is, het dit nog nie veel sukses behaal nie. Dit vereis deeglike beplanning en die proses moet deurgaans gemonitor word tydens die implementasie daarvan. So word areas wat gewysig of verander moet word, geidentifiseer. Regstellende aksie moet nie verwar word met vergelding, waar blankes gestraf word vir die voorregte wat hul geniet het nie. Dit beteken nie dat blanke werknemers van hul posisies verwyder word en deur swartmense vervang moet word nie. Dit kan lei tot rassekonflik en verbittering aanmoedig. Regstellende aksie vereis opleiding en die onwikkeling van lede van voorheen benadeeide groepe, sodat hulle voorberei word om die beroepsleer te bestyg. Hulle moet 'n aktiewe rol in hul eie ontwikkeling speel. Die "kultuur van -gereg-ti-gheid" wat die gedagtes van die histories benadeelde groepe oorheers moet uitgeroei word. Daar moet nie dangeneem word dat die wat voordeel trek uit die regstellende proses geregtig is tot bestuursposisies, sonder die nodige kwalifikasies of vaardighede nie. Elke organisasie moet geleenthede voorsien vir die opleiding en ontwikkeling van benadeelde groepe, soos byvoorbeeld studieverlof, finansiele bystand en indiensopleiding. Akademiese instellings moet hulleerplanne aanpas om te voorsien in die behoeftes van die organisies. Toewyding deur topbestuur, werknemers en vakbonde is een van die belangrikste bestanddele waaruit regstellende aksie bestaan. Alle belangegroepe sal dan kan saamwerk in die ontwikkeling van strategiee vir die suksesvolle implementasie van regstellende aksie programme. Die kultuur en denkwyse in die wekplek moet verander. Daar moet 'n verandering in persepsies en houdings intree. Dit is noodsaaklik om at te sien van die rassistiese denkwyse dat enige iets van Afrika nie goed genoeg is nie. Die waardering en aanvaarding van kulturele verskille onder werknemers is noodsaaklik. Daardeur word bygedra tot die produktiwiteit en effektiwiteit van 'n organisasie. Die vaardighede van werknemers moet in ag geneem word om 'n verlaging van standaarde te voorkom. Waar die vorige bedeling werknemers met die nodige potensiaal van sekere kwalifikasies en nodige ondervinding ontneem het, word hulle nou opgelei om hul volle potensiaal te bereik. 'n Organisasie moet, waar moontlik, die dienste van 'n regstellende aksie toesighouer of senior bestuurder, wat tot die pligte van 'n regstellende aksie toesighouer aangestel is, gebruik maak. Die toesighouer moet verkieslik 'n lid van die benadeelde gemeenskap wees. Die persoon moet respekafdwing en as kredietwaardig binne die organisasie gesien word. Die toesighouer is verantwoordelik vir die hantering van vraagpunte wat rondom regstellende aksie mag ontstaan. Hy / sy moet in samewerking met 'n besturende regstellende aksie komitee optree. Die komitere moet uit 'n deursnee van personeel bestaan met gelyke verteenwoordiging van alle belangegroepe. Spesifieke programme moet ontwerp word om diskriminasie tydens menslike hulpbronaktiwiteite. soos werwing, keuring, bevordering, opleiding en ontwikkeling, asook evaluasie, teen te werk. Daar moet meganismes ingestel word om klagtes en verskille aangaande beweerde diskriminasie te hanteer. ___________________________________________________________________
Dissertation (M.P.A. (Public Management))--University of the Free State, 1998
Keywords: Affirmative action programs -- South Africa; Discrimination in employment -- South Africa